Reduced apoptosis of monocytes and macrophages is associated with their persistence in wounds of diabetic mice. (June 2021) - Pang, Jingbo; Maienschein-Cline, Mark; Koh, Timothy J.
Highlights: Mo/MΦ apoptosis parallels their reduction in wounds of non-diabetic mice. Reduced Mo/MΦ apoptosis linked to their persistence in wounds of diabetic mice. TNF, MAPK, Jak-STAT, and FoxO pathways associated with wound Mo/MΦ apoptosis. Abstract: Monocytes and macrophages (Mo/MΦ) rapidly accumulate in skin wounds after injury, then disappear as healing progresses. However, the mechanisms underlying their ultimate fate in wounds remain to be elucidated. Here, we show that apoptosis of Mo/MΦ parallels their reduction as wound healing progresses in non-diabetic mice. scRNAseq analysis confirmed enriched apoptosis GO pathways on day 6 post-injury in wound Mo/MΦ from non-diabetic mice. In contrast, there was significantly less Mo/MΦ apoptosis in wounds from diabetic mice, particularly in the pro-inflammatory Ly6C+ population, which may contribute to persistent Mo/MΦ accumulation and chronic inflammation. scRNAseq analysis implicated TNF, MAPK, Jak-STAT, and FoxO signaling pathways in promoting wound Mo/MΦ apoptosis in non-diabetic mice while cell proliferation related pathways appeared to be activated in diabetic mice. These novel findings indicate that reduced apoptosis is a contributor to persistent Mo/MΦ accumulation in diabetic wounds. These findings also highlight pathways that may regulate Mo/MΦ apoptosis during wound healing, which could be targeted to help resolve inflammation and improve healing.